Développement nordique et harmonie - Louis-Edmond Hamelin (Cahiers de géographie du Québec, 2005)
According to a northern index, southern limits of the North stand between latitudes 49 and 56 through Canada's mainland so, the North includes both Territories, the northern part of seven Provinces and all « interior » marine waters then it has several governments. A liaison policy has to be set up among ten northern political entities of Canada.Until now, northern developments were almost characterized by the opportunity syndrome. Motivation for making money was the key factor. Activities other then sectorial receive very little concern. Regions of the North have lived under the menace of being a prey of some entrepreneurs.Scientists cannot be satisfied with that kind of approach. A more wide range of preoccupations must be considered. Somehow, development is a comprehensive subject, not a thematic one. In the past, spotted schemes as an hydro plant, a quarry for mineral ore, a fishing lodge were not enough related to the region, to the local people, to the interest of the North as a whole.Political change as such be thought of. Harmoniously development cannot be achieved without a parallel and appropriated move in the administrative structure. It is not done yet. Inside Provinces, northern parts are ruied from a capital city with a very low level of participation by Northerners themselves. Inside both Territories, political growth is controlted by Ottawa and there is no direct contacts between southern economic prospects and territorial governments. Southernity and federality seem excessive.A perception test confirms that the North is short of convergence with the South and southern makers of decisions are short of nordicity. If the North is not an island and cannot be isolated, its specificity requires comprehension and adaptability. The North is not any part of Canada. Make profit and do things northerly could be different objectives. An harmonically development cannot be achieved without more « northness ». Le Nord canadien comprend deux territoires, la partie septentrionale de sept provinces et des ...